ANALISIS BIAYA PENDIDIKAN PERSONAL DAN PENGARUHNYA TERHADAP HASIL BELAJAR MAHASISWA PIPS FKIP UNIVERSITAS RIAU - Jefri, Muhamad; Gimin, Gimin; Syabrus, Hardysem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of the study is to know the effect of personal education costs on the learning outcomes of social science education students of FKIP UNRI. The population in this study was the entire student of social sciences education of UNRI for 216 students and samples to be researched as many as 122 students using simple random sample techniques 10% error rate. Data collection using questionnaires. Data analysis using simple linear regression analysis. The results showed that student learning results of the University of Riau PIPS which is 2016 including satisfactory, accumulative category of personal education cost of students are included in the low and very low category, based on the results Research and analysis of data using simple regression analysis of Personal education costs (X) and learning outcomes (Y) can be equation Y = 3.046 + 0.00000003953 X where the research results show that X simultaneously affects Y. Results Coefficient of determinant (R2) is 0.252. This means that the influence of education costs on the outcomes of students of the University of Riau FKIP PIPS is 0.252 or 25.2% while the remaining 74.8% is influenced by other factors that are not researched in this study. Therefore, adequate education costs and precise objectives will improve learning outcomes.Key Words: Cost of Personal Education, Learning Outcomes